Taming cannabis : drugs and empire in nineteenth-century France - Guba, David A., Jr., 1985- (Intoxicating histories, 2020)
"Despite having the highest rates of cannabis use in the EU, France today enforces the most repressive laws against the drug in all of Europe. But as David A. Guba, Jr. reveals, France once functioned as the epicenter of a global movement to medicalize cannabis, and specifically hashish, for the study and treatment of major diseases. Taming Cannabis examines how French authorities across the 19th century routinely blamed hashish consumption, and especially among Muslim North Africans, for a wide array of behaviors deemed irrationally violent and threatening to the social order of the French state. This association of hashish with irrational violence provided the primary impetus for French pharmacists and physicians to try to "tame" the drug and deploy it in the homeopathic treatment of mental illness and epidemic disease during the 1830s and 1840s. At first heralded as a "wonder drug" capable of curing insanity, cholera, and the plague, hashish proved ineffective against these diseases and fell from repute by the middle 1850s. However, the association between hashish and Muslim violence remained and became codified in French colonial medicine and law by the 1860s as a significant cause of mental illness, violence, and anti-state resistance among Indigenous Algerians. As the French government looks to reform the nation's drug laws to address the rise in drug-related incarceration rates and the growing popular demand in France for cannabis legalization, there is no better time than now to explore the largely untold and living history of cannabis and colonialism in France."--